FAKTOR YANG MEMPENGARUHI KEPUTUSAN ORANGTUA MENYEKOLAHKAN ANAK DI MIN 2 KOTA KEDIRI - Ummatul Khoiriyah; Ahmad Jauhar Fuad; Amik Nadziroh (cendekia citra gemilang, 2026)
The growing interest of parents in enrolling their children at MIN 2 Kota Kediri reflects a significant shift in educational orientation, emphasizing not only academic achievement but also the integration of spiritual and moral values. This study was conducted to examine the determinants of parental decision-making through a mixed methods sequential explanatory design. Quantitative data were obtained from questionnaires administered to 135 parents and analyzed using multiple linear regression, while qualitative data were gathered through in-depth interviews and thematically analyzed. The results indicate that all factors economic and access, religiosity, environment and facilities, social and cultural aspects, and teacher quality are significantly associated with parental decisions. Among them, religiosity (β = 0.443) and teacher quality (β = 0.262) were identified as the most influential. The coefficient of determination (R² = 0.666) demonstrates the robustness of the model. Parents ultimately expect their children to develop into pious individuals with noble character, prepared to face contemporary challenges in accordance with Islamic values.